2020
DOI: 10.1002/cbic.202000473
|View full text |Cite
|
Sign up to set email alerts
|

Selective Covalent Targeting of Anti‐apoptotic BFL‐1 by a Sulfonium‐Tethered Peptide

Abstract: Anti-apoptotic B cell lymphoma 2 (BCL-2) family proteins are proven targets for human cancers. Targeting the BH3-binding pockets of these anti-apoptotic proteins could reactivate apoptosis in BCL-2-depedent cancers. BFL-1 is a BCL-2 family protein overexpressed in various chemoresistant cancers. A unique cysteine at the binding interface of the BH3 and BFL-1 was previously proven to be an intriguing targeting site to irreversibly inhibit BFL-1 functions with stabilized cyclic peptide bearing a covalent warhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…BFL-1 includes highly conserved BH1 and BH2 domains and conserved BH3 and BH4 and can bond to proapoptotic proteins like NOXA and BID ( 44 ). It locates in mitochondria and performs anti-apoptotic functions ( 45 ). In addition, the proliferation of macrophages and mast cells in the allergic reaction ( 46 ) was promoted by BFL-1 binding to the Beclin-1 protein.…”
Section: The Structural Domains Of Bcl-2 Family Proteinsmentioning
confidence: 99%
“…BFL-1 includes highly conserved BH1 and BH2 domains and conserved BH3 and BH4 and can bond to proapoptotic proteins like NOXA and BID ( 44 ). It locates in mitochondria and performs anti-apoptotic functions ( 45 ). In addition, the proliferation of macrophages and mast cells in the allergic reaction ( 46 ) was promoted by BFL-1 binding to the Beclin-1 protein.…”
Section: The Structural Domains Of Bcl-2 Family Proteinsmentioning
confidence: 99%
“… 35 When such a peptide recognizes its target and if the protein has a Cys in the vicinity of the interacting interface, the peptide would bind to the protein with high selectivity and efficiency. 36 Based on this method, we first designed a series of sulfonium-tethered peptides to target SARS-CoV-2 PLpro, in which the main catalytic amino acid is the C111 residue. The PLpro recognized a conserved sequence with different substrates including the tetrapeptide LXGG motif found in between viral proteins nsp1 and nsp2, nsp2 and nsp3, and nsp3 and nsp4 for cleavage of the viral polypeptide.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we reported a unique bio-orthogonal reaction in which we tethered a peptide between Cys and Met with a newly formed sulfonium center . When such a peptide recognizes its target and if the protein has a Cys in the vicinity of the interacting interface, the peptide would bind to the protein with high selectivity and efficiency . Based on this method, we first designed a series of sulfonium-tethered peptides to target SARS-CoV-2 PLpro, in which the main catalytic amino acid is the C111 residue.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide did not conjugate to other Cys-containing proteins like PDZ, Bcl-2, MgrA, and sortase A. 104…”
Section: Cysteine (Cys)mentioning
confidence: 95%